Pembelajaran Berbasis Masalah dan Perencanaan Kurikulum - Nursantalia Habeahan; Gres Novelita Pakpahan; Damayanti Nababan (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Problem-Based Learning (PBL) has become a significant approach in the realm of education aimed at enhancing students' abilities to solve real-world problems. This paper delves into the integration of PBL within curriculum planning as an endeavor to create a more meaningful and pertinent learning environment for students. PBL amalgamates theoretical concepts with practical applications in problem-solving, enabling students to hone critical thinking, creativity, and collaborative skills. This research scrutinizes strategies for implementing PBL within curriculum planning, encompassing the identification of curriculum-relevant issues, structuring structured learning steps, and evaluating learning outcomes. The success of PBL within the curriculum context hinges upon schools' and teachers' capacities to design adaptable and flexible curricula. Teachers assume a pivotal role as learning facilitators, guiding students in exploring problems, fostering collaboration, and nurturing profound comprehension. Furthermore, this study underscores the advantages of integrating PBL into the curriculum, including heightened student motivation, fortified problem-solving skills, and preparing students to confront real-world challenges.